2023
DOI: 10.3390/coatings13121981
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Enhance Biomedical Device Performance and Safety: A Comprehensive Review

Julia Sánchez-Bodón,
Maria Diaz-Galbarriatu,
Leyre Pérez-Álvarez
et al.

Abstract: This paper reviews different approaches to obtain biomaterials with tailored functionalities and explains their significant characteristics that influence their bioactivity. The main goal of this discussion underscores the significance of surface properties in materials, with a particular emphasis on their role in facilitating cell adhesion in order to obtain good biocompatibility and biointegration, while preventing adverse effects, such as bacterial contamination and inflammation processes. Consequently, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 136 publications
0
2
0
Order By: Relevance
“…Thus, it confirmed again that the reaction took place successfully. Many studies, including our previous work, confirmed that surface chemical modification can alter the morphology and wettability properties of a surface [10,26,56]. Therefore, SEM and contact angle techniques were employed after every modification step in order to determine the topographical changes and water affinity of the surface (Figure 3).…”
Section: Plla Surface Preactivation and Tryptophan Immobilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it confirmed again that the reaction took place successfully. Many studies, including our previous work, confirmed that surface chemical modification can alter the morphology and wettability properties of a surface [10,26,56]. Therefore, SEM and contact angle techniques were employed after every modification step in order to determine the topographical changes and water affinity of the surface (Figure 3).…”
Section: Plla Surface Preactivation and Tryptophan Immobilizationmentioning
confidence: 99%
“…However, their slow degradation and high crystallinity can potentially cause inflammatory reactions in the body [ 8 ]. Furthermore, their hydrophobicity can induce biofilm formation, as bacteria tend to adhere to flat and hydrophobic surfaces [ 9 , 10 ]. Indeed, the issue of microbial contamination concerns multiple sectors ranging from food packing to medical devices [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some bioactive polymeric materials derived from natural organisms such as sodium alginate, hyaluronic acid, silk fibroin, gelatin, and chitosan have good biocompatibility and biodegradability, which are often used as matrix materials for wound dressings and artificial skin [ 230 ]. Synthetic polymers such as PEG, PVA and PLGA are somewhat less biocompatible and biodegradable than natural polymers, but they have better mechanical properties and customizability [ 231 ]. These polymer molecules often contain a large number of hydrophilic bioactive groups such as –OH, –COOH, –NH 2 , etc., which can modulate macrophage attachment, polarization, and cytokine secretion through interactions with immune cells, thereby reducing the occurrence of immune rejection [ 232 ].…”
Section: Property and Function Design Of Biomimetic Biomaterials For ...mentioning
confidence: 99%
“…MDPI and/or the editor(s) disclaim responsibility for any injury to people or property resulting from any ideas, methods, instructions, or products referred to in the content. purity, high density in coatings, excellent resistance to adhesion with the substrate and smooth surfaces with roughness in the nanometer range [6,7]. The PVD process, in addition to improving mechanical and electrochemical properties, offers advantages such as durability, costs and effectiveness compared to an uncoated part; It is also important to take into account the price of the complete equipment, performance and reliability, operating costs, the useful life of the equipment among others such as dimensions of the part to be coated and the environmental impact compared to other techniques.…”
Section: Introductionmentioning
confidence: 99%